2018
DOI: 10.1002/wps.20577
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions to reduce positive symptoms in schizophrenia: systematic review and network meta‐analysis

Abstract: Psychological treatments are increasingly regarded as useful interventions for schizophrenia. However, a comprehensive evaluation of the available evidence is lacking and the benefit of psychological interventions for patients with current positive symptoms is still debated. The present study aimed to evaluate the efficacy, acceptability and tolerability of psychological treatments for positive symptoms of schizophrenia by applying a network meta-analysis approach, that can integrate direct and indirect compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
115
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 83 publications
4
115
1
3
Order By: Relevance
“…Where the two meta‐analyses diverged, however, was in relation to the findings in blind trials. Bighelli et al continued to find a significant effect against treatment as usual (−0.27; 95% CI: –0.41 to −0.13) in 15 blind trials, but not against inactive control (−0.14; 95% CI: –0.37 to 0.09), although the number of studies here was smaller (n=5). In contrast, Jauhar et al found that the pooled effect size for positive symptoms against all controls dropped to very low levels in their sub‐analysis of 20 blind trials (–0.08; 95% CI: –0.18 to 0.03).…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Where the two meta‐analyses diverged, however, was in relation to the findings in blind trials. Bighelli et al continued to find a significant effect against treatment as usual (−0.27; 95% CI: –0.41 to −0.13) in 15 blind trials, but not against inactive control (−0.14; 95% CI: –0.37 to 0.09), although the number of studies here was smaller (n=5). In contrast, Jauhar et al found that the pooled effect size for positive symptoms against all controls dropped to very low levels in their sub‐analysis of 20 blind trials (–0.08; 95% CI: –0.18 to 0.03).…”
mentioning
confidence: 66%
“…Of clear relevance here is a network meta‐analysis of psychological interventions in schizophrenia published in this journal which found pooled evidence that CBT is effective against positive symptoms. On the contrary, a 2014 meta‐analysis by Jauhar et al failed to find clear evidence of effectiveness against this class of symptoms.…”
mentioning
confidence: 99%
See 3 more Smart Citations